2013
DOI: 10.1097/mph.0b013e31828e5281
|View full text |Cite
|
Sign up to set email alerts
|

A Child With Epstein-Barr Virus-associated Hemophagocytic Lymphohistiocytosis Complicated by Coronary Artery Lesion Mimicking Kawasaki Disease

Abstract: There is considerable overlap between hemophagocytic lymphohistiocytosis (HLH) and Kawasaki disease (KD) in terms of aberrant immune response though the etiology of KD remains unknown. We present a case fulfilling the criteria of both HLH and KD complicated by coronary artery dilatation: HLH was confirmed to be triggered by Epstein-Barr virus. This case alarms us the possibility that even patients with HLH may be complicated by coronary artery lesion, which is one of the hallmarks of KD. We would like to draw … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…As stated previously, both KD and EBV-HLH are autoinflammatory diseases complicated by immunologic dysfunction. There is considerable overlap between these conditions in terms of pathophysiology, such as increased serum levels of IL-6, IL-8, TNF-α and soluble IL-2 receptor [12]. Some studies indicated that EBV-infected CD8 + T cells and high levels of the cytokines in EBV-HLH may play some role in development of coronary artery lesions [12,13].…”
Section: Cardiovascular Complicationsmentioning
confidence: 99%
“…As stated previously, both KD and EBV-HLH are autoinflammatory diseases complicated by immunologic dysfunction. There is considerable overlap between these conditions in terms of pathophysiology, such as increased serum levels of IL-6, IL-8, TNF-α and soluble IL-2 receptor [12]. Some studies indicated that EBV-infected CD8 + T cells and high levels of the cytokines in EBV-HLH may play some role in development of coronary artery lesions [12,13].…”
Section: Cardiovascular Complicationsmentioning
confidence: 99%
“…Because the symptoms and signs of these diseases are nonspecific, certain clinical parameters should be investigated carefully. The presence of CAE is a strong indication for KD, but it is also found in HLH that fulfills the criteria for KD (22) or SoJIA (23)(24)(25)(26)(27). Age-based anemia, low serum albumin, elevated ALT, and elevated leukocytes are supplemental laboratory criteria for diagnosing IKD in patients with elevated CRP and ESR, with a normal echocardiogram (28,29).…”
Section: Discussionmentioning
confidence: 99%
“…Although several etiologies have been suggested to be involved in HLH, to date only one EBV-HLH case with a coronary artery aneurysm has been reported [5]. The previously reported EBV-HLH case fulfilled the diagnostic criteria of Kawasaki disease and was initially treated with high-dose intravenous immunoglobulins and oral aspirin.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that KD can cause arteritis resulting in coronary aneurism. Coronary artery aneurism was observed in the patients with HLH, who fulfilled the diagnostic criteria of KD [5]. …”
Section: Introductionmentioning
confidence: 99%